2016
DOI: 10.2169/internalmedicine.55.5122
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Antidiuretic Hormone Associated with Eosinophilic Granulomatosis with Polyangiitis

Abstract: A 78-year-old woman with a history of bronchial asthma presented with distal dominant sensory disturbance and weakness in the upper and lower extremities. A biopsy of the left peroneus brevis muscle showed active vasculitis with inflammation extending into muscle fascicles and fibrinoid necrosis of the vessel wall, consistent with eosinophilic granulomatosis with polyangiitis (EGPA). Despite her decreased serum osmolarity, her serum antidiuretic hormone level was not reduced, consistent with the syndrome of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…SIADH can be associated with a large number of underlying pathologies, with central nervous system disturbances, malignancies and drugs being the most common etiologies 4. However, we were able to find only three cases of SIADH documented occurring in association with EGPA, all in Japan 5–7. Our patient was Caucasian.…”
Section: Discussionmentioning
confidence: 62%
“…SIADH can be associated with a large number of underlying pathologies, with central nervous system disturbances, malignancies and drugs being the most common etiologies 4. However, we were able to find only three cases of SIADH documented occurring in association with EGPA, all in Japan 5–7. Our patient was Caucasian.…”
Section: Discussionmentioning
confidence: 62%
“…Lundin et al [ 6 ] reported a case of a 62-years-old male with hyponatremia resulting from the prolonged medication for allergic asthma with a serum sodium of 120 mmol/L and positive perinuclear anti-neutrophil cytoplasmic antibodies, ultimately considered to result from the syndrome of inappropriate antidiuretic hormone eliciting eosinophilic granulomatosis and polyangiitis. In addition, Tokushige et al [ 7 ] demonstrated that polyangiitis may cause some damage to the hypothalamus or posterior pituitary, inducing arginine vasopressin dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…EGPA could be associated with inappropriate antidiuretic hormone syndrome[59]. EGPA categorized into two different clinical phenotypes according to the type/level of autoantibodies patient serum, ANCAnegative EGPA and anti-MPO-ANCA EGPA.…”
mentioning
confidence: 99%